Dinamika Perkembangan Sosial Ekonomi dalam Implementasi Hukum Waris Adat Jawa - Nurgianto, Dwi; Al Amin, Habibi (Kartika: Jurnal Studi Keislaman, 2025)
This study aims to analyze the influence of socio-economic development on the implementation of Javanese customary inheritance law. The research was conducted using a non-doctrinal (empirical) legal research method with a micro-theoretical symbolic interactionism approach. Data were collected through in-depth interviews and supported by purposive sampling techniques to select informants who were considered relevant to the research objectives. The results show that socio-economic transformation, particularly the shift of livelihoods from agriculture to industrial and trade sectors, has significantly affected inheritance practices within the community. The implementation of Javanese customary inheritance law is carried out through two main mechanisms, namely voluntary distribution based on personal willingness and distribution based on mutual agreement among family members. The voluntary method is primarily influenced by social status and the value of darma bakti, while the agreement-based method emphasizes the maintenance of family harmony. Furthermore, in cases of non-compliance with customary inheritance norms, the community applies customary law as a form of social control through conciliatory and remedial mechanisms. These findings indicate that Javanese customary inheritance law is experiencing adaptive changes in response to modern socio-economic dynamics, highlighting the need for contextual adjustments while preserving core customary values.